EVALUATION OF THE MICRODILUTION METHOD FOR DETERMINATION OF THE MINIMUM INHIBITORY CONCENTRATION (MIC) OF TERBINAFINE AGAINST TRICHOPHYTON RUBRUM - Thalia Anggrea Noor; Delly Chipta Lestari; Conny Riana Tjampakasari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Trichophyton rubrum is the leading cause of dermatophytosis with a global prevalence of 50–90%. Terbinafine is a first-line therapy that works by inhibiting the squalene epoxidase enzyme in ergosterol biosynthesis. Accurate determination of the minimum inhibitory concentration (MIC) using a standardized susceptibility test method is necessary to ensure the effectiveness of therapy. This study aims to standardize the concentration of terbinafine using the microdilution method based on CLSI M38-A2 guidelines against Trichophyton rubrum ATCC MYA-4438. The test was carried out using an inoculum concentration of 1×10³–3×10³ CFU/mL with varying terbinafine concentrations , then incubated at 28–30°C for 3–4 days. The results showed MIC values of 0.125 µg/mL; 0.25 µg/mL; and 0.125 µg/mL, respectively. An essential agreement (EA) value of 100% indicates high method precision. Morphological analysis revealed changes in hyphal structure in the form of fragmentation, a decrease in the number of conidia, cytoplasmic clumping, and uneven cell walls due to squalene accumulation. Thus, the microdilution method proved valid and reproducible for determining the MIC of terbinafine against T. rubrum .